Democracy and democratization in contemporary Muslim societies: a theoretical analysis - Ra'ees, Wahabuddin (Research Center, IIUM, 2010)
This paper examines the impact of democracy and democratization on contemporary Muslim societies. The institutional and philosophical approaches to democracy and democratization are inseparable. The paper investigates the relationship between the philosophical dimension of Western democracy and the Muslim philosophy of life and concludes that the democratization of contemporary Muslim societies leads to serious and destabilizing ideological polarization and division of Muslim societies into supporters of secularism and political Islam. The Islamist-secularists relation radicalizes: (1) when the Islamists are prevented from capturing power through democratic institutions and (2) when the advanced Western democratic states cooperate with non-democratic secular elites of Muslim societies. The destabilizing role of democracy can be moderated if the Islamists are engaged in the democratic process, and the debate between the Islamists, the secularists and the West . based on the view that the West should conceive Islam as an alternative weltanschauung (worldview) . focuses on issues that are human properties, irrespective of religion, ethnicity or language. The institutional approach to democracy provides a common ground for cooperation and dialogue between the Islamists, the secularists and the West.